Application and Performance Evaluation of Chemical Coagulation, Electrocoagulation, Electro-Fenton and Anodic Oxidation Processes in the Treatment of Glass Fiber Manufacturing Wastewater - Buket Kar; Belgin Gozmen; Özkan Görmez (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study investigated the oxidation of wastewater generated during the production of glass fiber manufacturing material, which contains high organic carbon (18.32 g/L) and has a pH of 8.8, by chemical coagulation, electrocoagulation and electro-advanced oxidation techniques. It was determined that the total organic content (TOC) of wastewater was reduced by 53% using the chemical coagulation method. After electrocoagulation with Al/Al electrode pair for 300 minutes at 500 mA, 73% TOC removal was achieved at pH 8.8. While 50% TOC removal was completed in 2 h at 400 mA in electrocoagulation with Fe/Fe electrode pair, 71% TOC removal was obtained in the combined electrocoagulation/electro-Fenton process by adding hydrogen peroxide to the medium under the same conditions. In addition, it was also observed that the success of the anodic oxidation methods alone was lower. The electro-Fenton application after electrocoagulation was effective and provided 78% TOC but required work at pH 3 and a longer treatment time.